Social Accounting in Sustainability Reporting for Digital Banking - Suhardjo, Suhardjo; Junaedi, Achmad Tavip; Andi, Andi; Putri, Novita Yulia; Renaldo, Nicholas; Musa, Sulaiman; Cecilia, Cecilia (First Ciera Publisher, 2024)
This research explores the role of social accounting in sustainability reporting for digital banking, highlighting its importance, current practices, and potential improvements to enhance accountability and transparency. This study aims to bridge the gap between theory and practice by proposing a comprehensive framework for integrating social accounting into sustainability reporting for digital banking. The descriptive qualitative approach is suitable for examining complex phenomena. The qualitative data is analyzed using thematic analysis to identify recurring patterns and insights. The steps include data organization, thematic coding, pattern identification, and interpretation. The integration of social accounting into sustainability reporting for digital banking represents a critical step toward ensuring transparency, accountability, and alignment with global sustainability goals. This study highlights that leading digital banks are adopting social accounting practices to address financial inclusion, green financing, and community engagement.